BELONGING AND UNBELONGING SPACES OF THE TRIPURA BENGALIS: AN ANALYTICAL STUDY OF SELECT POEMS FROM THE MYSTIC MOUNTAIN-AN ANTHOLOGY OF TRIPURA- BANGLA POETRY IN ENGLISH - Chakraborty, Jagriti; Chakrabarty, Madhumita (International Journal of Research -GRANTHAALAYAH, 2023)
The former princely state Tripura, and its history stands different than other Bengali state like West Bengal. Their complex dynamics of belonging have been relegated to the margins until very recent times. There are various literary works which focuses upon the upheavals of Bengalis belonging to West Bengal or those who took refuge in West Bengal, but the situation of Tripura Bengalis is very less known. Hence the introductory segment of the paper might highlight the facts related to Tripura Bengalis, their arrival, and their stories of settlement. However, the purpose is to examine an epistemological study of history, the entire process of partition, their memories of lost home, and their settlement in Tripura. Partition was treated as an unwanted anomaly in the narrative of the otherwise successful national movement. It is the ’human dimensions’ of the partition and its consequences on Tripura Bengalis has been taken up in the current Study. The Bengali population of Tripura still is struggling to define their identity, reflecting on the constant oscillation between past and present, amidst change and continuity. The human cost of the multiple migrations in Tripura and its impacts will be attempted to redefine and explore through the concepts of ethnographic approaches, textual analysis, and Diaspora studies. The text taken up by the researcher include: The Mystic Mountain-An anthology of Tripura Bangla Poetry in English, focusing on Nostalgia, Identity- crisis and a sense of belonging.